(untitled) (Research, Society and Development, 2022)
Cardiovascular diseases are responsible for a large number of deaths every year, many of them of atherosclerotic origin characterized by the formation of atheromatous plaques in the walls of the arteries. Punica granatum L. is a rich source of bioactive compounds with action in pathologies of cardiovascular origin. Its antioxidant and antiatherogenic activity are responsible for the therapeutic action in the prevention and treatment of this disorder. Thus, the present study aimed to describe the benefits of using pomegranate in the fight against atherosclerosis and the pharmacological pathways through which the treatment is developed. This is an integrative bibliographic review carried out in the databases of the Virtual Health Library- BVS and PubMed, using the descriptors Punica granatum L., pomegranate and atherosclerosis in Portuguese, English and Spanish and combined with each other through the Boolean operator “AND”. The results showed the pomegranate’s positive response to cardiovascular diseases, as demonstrated in the studies used in this review. Concluding that the consumption of pomegranate contributes to the prevention and reduction of atherosclerotic plaques already installed.